Desarrollo de una biopelícula partiendo de cáscara de banano y fibra natural como agente de refuerzo a nivel laboratorio (2019)
This paper describes the development of a biofilm from banana peel and natural fiber as a reinforcing agent. Performing the extraction of starch of banana peel and endocarp by the dry method, to which he applied a qualitative and quantitative test to confirm the presence and starch content, with a yield of 7.3% and 6.5%. With the objective of development the biofilm by selecting the natural fiber from its resistance to traction and elongation, which was easily accessible and economical.